Verification of the Dynamic Modeling of 2-R Robot Actuated by (N) Equally Spaced Planet-Gears by Using SolidWorks and MATLAB/SIMULINK - Fernini, Brahim; Temmar, Mustapha; Kai, Yoshihiro; M. M., Noor (Lodz University of Technology, 2018)
Industrial robots often use planetary gear system to have high joint torques; therefore, the influence of the rotary inertia of the number of the equally spaced planet-gears on the dynamical behavior of the robot is very important. The main objective of this paper is to develop the dynamic modeling of robot actuated by (n) equally spaced planet-gears in the case where the planet-carrier is fixed, no closed solution has been reported for this dynamic modeling, and to compare between the dynamic behavior of robot actuated by (n+1) and (n) equally spaced planet-gears for a same trajectory planning. The authors derive the explicit dynamic model for an elbow down of 2-R manipulator holding an external mass. Finally, the obtained simulation results by using Matlab/Simulink of the dynamic modeling are verified by modeling the same robot and using an advanced simulation via SolidWorks (2014).